Peran Guru PPKn Dalam Menumbuhkembangkan Nilai Karakter Demokratis Pada Peserta Didik Kelas IX di SMP Negeri 1 Mojolaban Sukoharjo - Dany Satria Aji; Yusuf Yusuf; Sugiaryo Sugiaryo (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2022)
The aims of this study are: (1) To determine the values ​​of democratic character in SMP Negeri 1 Mojolaban (2) To analyze the role of PPKn teachers in developing democratic character values ​​in students at SMP Negeri 1 Mojolaban. This research was conducted at SMP Negeri 1 Mojolaban. The subjects of this research include principals, vice principals, PPKn teachers, and students. The data source uses primary data sources and secondary data sources. Data was collected through interviews, observation, and documentation. The validity of the data was tested by triangulation, both techniques and sources. The research data were analyzed using interactive model qualitative analysis techniques. Based on the results of data analysis, it can be concluded that: (1) at SMP Negeri 1 Mojolaban has implemented democratic character values, by integrating democratic character values ​​in each subject so that students are accustomed to applying democratic character values, (2) teachers at SMP Negeri 1 Mojolaban has carried out its role well, it can be shown that the teacher always provides encouragement, motivation and habituation to students in developing the value of the character of honesty.